Activated carbon-gravity driven biomimetic membrane (AC-GDBM) for organic micro-polluted water treatment. (1st October 2021) - Chen, Wensong; Luo, Jiaming; Du, Xing; Ding, Luhui; Zhang, Wenxiang
Abstract: Gravity-driven biomimetic membrane (GDBM) has been developed as a promising membrane separation technology regarding ecological water treatment. Given its catalytic function on micro-pollutant removal and fouling control, detailed mechanism for fabrication material influence, organic micro-pollutants (OMPs) degradation, and operation strategy optimization have not been clear so far. In this work, the GDBM performance with various activated carbon (AC) materials (wood, coal, column and powder AC), and hydrostatic heights were investigated and verified. The activated carbon-gravity driven biomimetic membrane (AC-GDBM) fabrication tests demonstrated that AC-GDBM with powdered wooden AC had better filtration performance (up to 55 LMH flux and 97.5% removal rate) than AC-GDBM with other ACs. Furthermore, the effects of operation strategies (AC dosage, lacasse dosage, carbamazepine (CBZ) concentration, hydraulic height and rotating speed) on the filtration performance of AC-GDBM were conducted. At 25 g m −2 AC dosage, 30 g m −2 lacasse dosage, 10 mg L −1 CBZ concentration, and 5 cm hydraulic height, the optimized flux and removal rate were obtained. Further investigation revealed the surface morphology and property of AC-GDBM, displaying that powdered wooden AC and laccase formed the even biomimetic layer on base membrane. Additionally, for treating various OMPs (CBZ, tetracycline hydrochloride (TET), quinolones (norfloxacin (NFX)), and sulfonamides (sulfamethoxazole (SMZ))), with the optimized conditions, the removal rate and flux of AC-GBDM could maintain at high levels. This study demonstrates an example of a niche application, where GDBM is expected to offer a highly efficient and cost-effective ecological water treatment technology. Graphical abstract: Image 1 Highlights: Gravity-driven biomimetic membrane (GDBM) was used for organic micro-pollutant removal. Powdered wooden AC was the best fabrication material (55 LMH flux and 97.5% removal rate). Increasing hydraulic height strengthened the flux within the critical flux range. Powdered wooden AC and laccase formed the even biomimetic layer on base membrane. AC-GDBM can effectively remove various organic micro-pollutants.